A Survival Analysis with Cox Regression Interaction Model of Type II Diabetes Mellitus in Indonesian - Simeftiany Indrilemta Lomo; Sugiyarto Sugiyarto; Endang Darmawan (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2021)
Type II diabetes mellitus is a metabolic syndrome characterized by hyperglycemia. Diabetes is still one of the world's health threats where the number of people with disabilities and mortality rates continue to increase over time. This study aims to analyze the survival of patients with type II diabetes mellitus as well as factors that affect it using survival analysis.  This study used medical record data of type II diabetes mellitus patients undergoing treatment for the period 2015-2019 at PKU Muhammadiyah Gamping Hospital and PKU Muhammadiyah Hospital Yogyakarta.